Obstacles in implementing the independent curriculum in elementary schools - Daga, Agustinus Tanggu; Bili, Fransiskus Ghunu; Gena, Engelbertha Halena (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research is motivated by the urgency of understanding the obstacles in the implementation of the Independent  curriculum. The reality shows that the implementation of the Independent curriculum faces various obstacles. The aim of this study is to explore the obstacles faced by teachers when applying the Independent Curriculum in elementary schools. The method used is a literature review. Data was gathered from articles published between 2022 and 2024 through platforms Google Scholar, ResearchGate, and Garuda Kemdikbud. A total of 30 articles were identified, with 11 found to be relevant to the research topic. Data analysis includes determining the topic and research questions, collecting literature, developing inclusion and exclusion criteria, reading and analyzing the literature, synthesizing and organizing the information, and writing and revising the document. The results of the article reviews indicate that teachers face obstacles in implementing the independent curriculum during planning, execution, and assessment activities. These obstacles stem from local government, school principal's policies, and the capacity of teachers. The findings of this research are significant for teachers as a thorough understanding of these challenges can aid in developing more effective policies and strategies related to the Independent Curriculum, thereby enhancing its implementation in elementary schools.